Halal Tourism By Stakeholder’s Perspective - Sofiah, Sofiah; Khumaidah, Sofkhatin; Fauzan, Fauzan (IQTISHODUNA: Jurnal Ekonomi Islam, 2023)
This paper aims to identify halal tourism from the views of stakeholders.  Considering that halal tourism is currently the main industry that contributes to increasing the country's economic growth, various stakeholders' points of view are needed in identifying the meaning of halal tourism. This paper uses narrative Literature Review by searching for research journals related to halal tourism on the Google Scholar database. Data was taken for the last 5 years starting from 2017 to 2021. This paper analyzes the halal tourism in various perspectives 1) The government describes that halal tourism is one of the strategies or branding to attract foreign tourists, so that the country's foreign exchange and tourism development in Indonesia are increasing. 2) The Ulama describe that branding of destination as halal tourism is not important, the most important thing is that tourism can provide halal services so that it makes Muslim tourists comfortable in traveling, 3) The destination managers and Muslim minorities state that halal tourism does not need to be embedded in destination services because it will reduce tourist interest. The results of this study can contribute to stakeholders in developing halal tourism in Indonesia, because halal tourism is a new concept, it needs specific thinking for stakeholders in making policies related to halal tourism.